2022
DOI: 10.1108/ccij-10-2022-0120
|View full text |Cite
|
Sign up to set email alerts
|

What is an equitable target percentage for women on corporate boards?

Abstract: PurposeThe corporate communications literature recently raised the question, “Board gender diversity and women in leadership positions – are quotas the solution?” This paper extends the debate by asking, “What is an equitable target percentage for women on corporate boards?”Design/methodology/approachThe paper explores and gives a conceptualised viewpoint on the issues expressed in the literature concerning the meaning of board gender equality, focussing on what is regarded as an equitable number of women on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 63 publications
(125 reference statements)
2
14
0
Order By: Relevance
“…Matsa and Miller also observed that younger female directors replaced younger men and did not, therefore, decrease the board's average age structure. However, it was soon realised that some more qualified women had qualities that may enhance board decision-making (Lefley and Jane cek, 2022). Seierstad et al (2020) observed that although women were initially invited to join corporate boards just to build up the numbers, this eventually changed with companies becoming more selective.…”
Section: Previous Quota Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…Matsa and Miller also observed that younger female directors replaced younger men and did not, therefore, decrease the board's average age structure. However, it was soon realised that some more qualified women had qualities that may enhance board decision-making (Lefley and Jane cek, 2022). Seierstad et al (2020) observed that although women were initially invited to join corporate boards just to build up the numbers, this eventually changed with companies becoming more selective.…”
Section: Previous Quota Experiencementioning
confidence: 99%
“…The corporate communications literature recently focussed on corporate board gender diversity, specifically looking at two central aspects: gender quotas and equitable target percentages for women on corporate boards (Hamplov a et al, 2022;Lefley and Jane cek, 2022). Hamplov a et al (2022) investigate if quotas will solve the issue of the lack of women on corporate boards and conclude (p. 752), "the evidence from this research shows that while quotas may not be a panacea and may not eliminate gender discrimination, they could tip the equilibrium towards greater equality".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, this study concurs with the idea that women are still a minority in newspaper boardrooms (Byerly, 2013; Byerly and McGraw, 2020). Furthermore, and as Lefley and Janecek (2022) recently put it, the target should not just be to place women in what is currently a masculinized board culture but to change this culture to reflect non-masculinity.…”
Section: Discussionmentioning
confidence: 99%
“…The experience of quotas within the EU has been well documented by Mensi-Klarbach and Seierstad (2020), while Hamplov a et al (2022) ask, are quotas the solution? Lefley and Jane cek (2023a) raise the question of what is an equitable target percentage for women on corporate boards. Gender quotas requiring women to be included in leadership positions, including on corporate boards of leading companies, have flourished (Latura and Weeks, 2023).…”
Section: Introductionmentioning
confidence: 99%